RESPONSES OF EGGPLANT (SOLANUM MELONGENA L.) TO DIFFERENT RATES OF NITROGEN UNDER FIELD CONDITIONS - Mohammad HOSSEIN AMINIFARD (Journal of Central European Agriculture, 2011)
The present study was carried out to evaluate the effect of nitrogen fertilizer on growth and yield of eggplant (Solanum melongena L.) under field conditions. Nitrogen was applied in four rates (0, 50, 100 and 150 Kg/ha). Average plant height, lateral stem number, leaf chlorophyll content, flower number, fruit weight and plant yield were determined , Increasing rates of Nitrogen significantly affected plant vegetative growth (plant height, lateral stem number, and leaf chlorophyll content).The highest lateral stem number and leaf chlorophyll content were obtained in plants receiving 150 Kg N ha -1. Nitrogen fertilizer affected flower number and the days to first flowering. Nitrogen application decreased the days to first flowering and treated plants flowered early than control. It was observed that fertilization with 100 Kg N ha-1 resulted in the highest average fruit weight and fruit yield. Our results showed that nitrogen fertilization has strongly influenced vegetative and reproductive growth of eggplant plants grown under field conditions.